Predictors of excess return in a green energy equity portfolio: Market risk, market return, value-at-risk and or expected shortfall? - Rebecca Abraham; Hani El-Chaarani; Zhi Tao (Journal of Risk and Financial Management, 2022)
The rapid growth of electric vehicles, solar roofs, and wind power suggests that the potential growth in green equity investments is an emerging trend. Accordingly, this study measured the predictors of excess equity returns in a portfolio of global green energy producers, from 2010 to 2019. Fixed-effects panel data regressions of daily returns, followed by quantile regressions, were performed. There was some support for the explanation of green equity returns by market returns and market risk (beta), as indicated by the single-factor Capital Asset Pricing Model (CAPM), and the multifactor Fama-French Three-Factor and Fama-French Five-Factor Models. The most significant predictors of green equity returns were Value-at-Risk at a 95% confidence level, and Value-at-Risk at a 99% confidence level. Expected Shortfall was another extreme risk value measure. The importance of extreme value measures suggests the presence of fat-tailed leptokurtic distributions, whereby excess returns were explained by the risk of loss given adverse conditions, primarily at 95% confidence. We conclude that the proliferation of small firms and new entrants in the renewable energy sector has led to the explanation of returns by extreme values of risk.
Keywords: 330; green equities; Capital Asset Pricing Model; Fama-French Three-Factor Model; Fama-French Five-Factor Model; Value-at-Risk; Expected Shortfall